1984
DOI: 10.1002/jcp.1041180306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular smooth muscle cell migration by heparin‐like glycosaminoglycans

Abstract: Previous studies have suggested that heparin-like glycosaminoglycans may be endogenous inhibitors of smooth muscle proliferation in the vessel wall. The purpose of this study was to determine the effects of exogenous glycosaminoglycans on rat vascular (aortic) smooth muscle cell migration following wounding in vitro. Our data indicate that heparin and related molecules (iota carrageenan, dextran sulfate), but not other glycosaminoglycans (hyaluronate, chondroitin, and dermatan sulfates), inhibit smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(98 citation statements)
references
References 22 publications
4
94
0
Order By: Relevance
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 84%
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 84%
“…In the first, migration was measured using a monolayer-wounding protocol in which cells migrated from a confluent area into an area that was mechanically denuded of cells. 21 In the second type of assay, collagen-coated transwell tissue culture inserts composed of a polycarbonate membrane containing 8-m pores were used. This assay method determines cell chemotaxis.…”
Section: Migration Assaysmentioning
confidence: 99%
“…103 Little is known about the factors that control this process. Recent studies by Majack and Clowes 132 have shown that heparin inhibits arterial smooth muscle cell migration in vitro in a dose-dependent and reversible fashion, but hyaluronate and chondroitin or dermatan sulfate do not. Furthermore, this effect was specific for arterial smooth muscle cells, since similar 29 Shaded areas represent proportion of total radioactivity present in the cell layer.…”
Section: Cell Migrationmentioning
confidence: 99%